Farmers’ preferences for Peste des petits ruminants disease vaccine delivery attributes in Uganda - Lule, Peter Mulindwa; Otieno, David Jakinda; Nyikal, Rose Adhiambo; Namatovu, Jane; Kiara, Henry; Roesel, Kristina; Ouma, Emily (Frontiers in Veterinary Science, 2025)
Small ruminants in Uganda are affected by a highly contagious disease called Peste des petits ruminants (PPR), commonly referred to as goat plague. It is highly contagious and has high mortality and morbidity. The disease can be controlled through vaccination, but the vaccine is not readily available and accessible in the Ugandan market, especially in the areas where the PPR problem has been identified. Furthermore, farmers tend to believe that vaccination is the mandate of the government, who should therefore bear the cost of its delivery. Therefore, the drivers of vaccination delivery become very important if the country is to eradicate PPR by 2030 as committed. This study analyzed the vaccine delivery attributes that farmers prefer in three districts of Uganda representing three production systems (pastoral, agro-pastoral and mixed crop-livestock). The study randomly sampled 444 small ruminant rearing households and used discrete choice experiments to elicit preferences. Both the random parameter logit and the latent class random parameter logit were used to analyze preferences. Farmers’ willingness to pay and the compensating surplus for different attributes and policy scenarios were estimated. The results indicated that the farmers preferred to obtain certificates after vaccination. In addition, farmers preferred closer vaccination stations to their homes and vaccination by qualified personnel. Farmers were willing to pay the highest for vaccine certification. The study recommends the provision of certificates after vaccination to allow farmers to move their animals even when quarantines are imposed as an incentive to increase vaccine coverage. Also, the participation of different stakeholders in conducting awareness campaigns for vaccination, especially with respect to the provision of quality vaccines is paramount. Lastly, the government should subsidize costs associated with administering the vaccine.